Cognition and Deep Brain Stimulation Consensus Conference Decision to Treat Primary Dystonia. (16th November 2020) - Marotta, Dario A; Niccolai, Lindsay; Aita, Stephen; Walker, Harrison; Del Bene, Victor; Gerstenecker, Adam; Gammon, Meredith; Martin, Roy; Clay, Olivio; Crowe, Michael; Triebel, Kristen
Abstract: INTRODUCTION: Deep brain stimulation (DBS) is an effective treatment for motor disturbance in patients with primary dystonia. Candidacy and appropriateness of DBS therapy is determined by an interdisciplinary consensus conference after considering numerous demographic, medical, cognitive, and behavioral factors on an individual basis. However, little is known about which of these factors are associated with consensus conference decisions. METHODS: Thirty-two patients with primary dystonia completed comprehensive neurological and neuropsychological examinations in consideration for potential DBS surgery. Demographic and medical data (e.g., dystonia disease characteristics, medical comorbidities, medications) were also collected. An interdisciplinary conference committee comprised of representatives from neurology, neuropsychology, nursing, and neurosurgery determined DBS therapy eligibility based on these data. Patients were grouped based on DBS conference decision (eligible: n = 21, ineligible: n = 11) and compared across demographic, medical, cognitive, and behavioral variables. To quantify medical disease factors, we used a modified Revised Cardiac Risk Index. RESULTS: Across clinical variables, patients who were deemed ineligible for DBS surgery had a higher modified Revised Cardiac Risk Index. Patients who were classified as ineligible displayed lower global cognitive functioning, working memory, phonemic fluency, memory retrieval, and cognitive flexibility. CONCLUSION: Deficits in executive functioning were closely associated with DBS consensus committee decisions. Incidentally, we observed elevated cardiac risk among these individuals, likely reflecting the relationship between vascular health and cognition. Executive functioning may be an important target for intervention to improve surgical candidacy for DBS in patients with primary dystonia.